2014
DOI: 10.1007/s00231-014-1306-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the reduction of NO to N2 by reaction with Fe under fuel-rich and oxidative atmosphere

Abstract: The limitation of nitrogen oxides (NO x ) emissions from stationary combustion chambers is still an important issue in the field of the natural environment protection. This paper describes the reduction of NO x in the presence of iron. A few new aspects of research describing the utilization of iron as an additive that influences NO x reduction at high temperatures are presented. In particular, the influence of the excess air number (k) on the NO x removal efficiency in the presence of Armco iron was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…It can be inferred from the traverse profiles (Figure 8a The collected fly ash from the pilot scale facility was subjected to analysis using the scanning electron microscope with energy dispersive spectroscopy. Table 7 magnetite at about 700 o C has also been reported by other researchers [29][30]34 .…”
Section: Kw Th Furnace Test Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It can be inferred from the traverse profiles (Figure 8a The collected fly ash from the pilot scale facility was subjected to analysis using the scanning electron microscope with energy dispersive spectroscopy. Table 7 magnetite at about 700 o C has also been reported by other researchers [29][30]34 .…”
Section: Kw Th Furnace Test Resultssupporting
confidence: 81%
“…The reduction of NO by combustion intermediate i.e. CO over the surface of oxides of iron [11][12][27][28][29] was validated by the recorded radial and axial profile measurements from the pilot scale 100kW th furnace combustion tests at 15% excess air for 3.4% by vol. addition of the additive.…”
Section: Kw Th Furnace Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning, NO reduction was 95%; however it decreased to about 20% after 5.05 h, as showed in Fig 7. This showed that CO was not good reductant in long-term application. Lasek [16] recently reported his research on NO reduction over iron sphere when CO was used as the reducing agent and the result showed that no more than 60% of NO was reduced when the air excess ratio was 0.6. When NO reduction efficiency was below 20%, CO was stopped and 1.17% CH 4 was fed into the reactor.…”
Section: Continuous No Reductions Over Iron Oxides With Co/chmentioning
confidence: 98%
“…Gradon and Lasek [15], Lasek [16] and Su et al [17,18] demonstrated that metallic iron could reduce NO to N 2 while the iron was oxidized to iron oxides. Hayhurst and Ninomiya [19], Hayhurst and Lawrence [20] found that Fe or Fe 2 O 3 could catalytically reduce NO to N 2 in a fluidized bed reactor (700-900°C) when CO gas existed.…”
Section: Introductionmentioning
confidence: 99%